THE INFLUENCE OF EDUCATION, AGE AND INFORMATION SOURCES ON PREGNANT WOMEN'S KNOWLEDGE ABOUT EARLY DETECTION OF IMMINENT ABORT AT THE HOSPITAL MIDWIFERY POLYCLINIC BHAYANGKARA BRIMOB 2023 - Puspita, Infi Dian; Futriani, Elfira Sri (HEARTY, 2024)
Background: Based on data on the number of abortions at Bhayangkara Brimob Hospital in the last 3 years, namely in 2020 there were 13 patients, in 2021 there were 21 patients and in 2022 there were 41 patients. From this data, it was found that the cause of the increase in abortion rates was due to mothers' lack of knowledge regarding early detection of imminent abortion. Research Objectives: To determine the influence of education, age and sources of information on pregnant women's knowledge about early detection of imminent abortion at the Obstetrics Polyclinic at Bhayangkara Brimob Hospital in 2023 Research Method: The research method used in this research is quantitative methods. This research includes cross sectional data. The population in this study was 40 pregnant women in the first trimester. The sample in this study was 40 respondents. The sampling technique is total sampling. Researchers used the chi-square test with a confidence level of 95% and a significance level of 5% respectively. Research Results: The results of the research show that the knowledge picture is good, namely 57.5%, the age of pregnant women is more 20 - 35 years old, namely 65%, the education of pregnant women is more secondary education, namely 65%, and the sources of information are more good sources of information. namely 55%. Statistical test results of education on knowledge P value = 0.007, age on knowledge P value = 0.015 and sources of information on knowledge P value = 0.000. Conclusions and Suggestions: There is an influence of education, age and sources of information on pregnant women's knowledge about early detection of imminens abortion at the Obstetrics Polyclinic of Bhayangkara Brimob Hospital in 2023. Suggestions for Hospitals Create educational classes for patients, especially pregnant women, to be able to understand about early detection incidence of imminent abortion